(untitled) (European Journal of Pure and Applied Mathematics, 2025)
Making use of the principle of subordination, we define a certain subclass of p-valently Bazilevič and non-Bazilevič functionsassociated with the Lemniscate of Bernoulli. Also, subordination results, inclusion relationship, convolution properties, coefficients estimate and Fekete–Szegö inequalities for this subclass are derived.